Acute Aortic Thrombus with Splenic Infarction in a Patient with COVID-19 Infection - Singh, Priya; Pratap Singh, Surya (Journal of Medical Science, 2021)
Acute Aortic thrombus with splenic infarction is a rare complication of COVID-19. This manuscript highlights the importance of early identification of this complication with abdominal imaging and early initiation of anticoagulation despite moderate severity of the disease.
Keywords: COVID-19; Splenic infarcts; Acute Aortic thrombus